Terrestrial and Freshwater Invertebrate Fauna of the High Arctic Archipelago of Svalbard - Coulson, Stephen James (Zootaxa, 2007)
An overview of the terrestrial and freshwater invertebrate fauna of the High Arctic archipelago of Svalbard is presented. Sixty seven additional species to the previous checklist are listed and the described terrestrial and freshwater invertebrate fauna of Svalbard now stands at 1,107 species. Species presented are cross referenced to the literature.        A brief comparison with the invertebrate fauna of Greenland indicates that Svalbard may be under-represented in Hymenoptera, Hemiptera and Lepidoptera but over-represented in Collembola and Acari. However, since 82% of Svalbard primary source manuscripts originate from three locations along the west coast, there is a resulting likely bias in our knowledge of the invertebrate fauna. The west coast has a mild climate for the northerly latitude due to the influence of the West Spitsbergen Current, a northerly flowing branch of the North Atlantic Drift. The faunistically poorly known east coast is hypothesised to have a different invertebrate fauna due to the predominant winds and currents originating from the north east and hence this coast will have a different history of immigration and colonization from the west coast.        The use of checklists is therefore cautioned due to possible sampling bias and omissions created by a concentration of work on popular groups and at a limited number of localities. However, this does not detract from their importance as baseline databases, especially during a period of rapid environmental change.